Multiple hallucinations due to brainstem injury: A case report - Silva,Melissa Castello Branco e (2010)
Abstract We report a case of a 43-year-old woman with brainstem encephalitis in the third trimester of pregnancy. She presented complex visual and auditory hallucinations in the acute disease phase (hearing opera arias and seeing room furniture upside-down). Hallucinations resolved with antiviral treatment.